When We Teach for Positive Creativity, What Exactly Do We Teach For? - Robert J. Sternberg; Aakash Chowkase (Education Sciences, 2021)
Positive creativity is creativity that makes the world a better place—that makes a positive, meaningful, and potentially enduring difference to the world. Positive creativity can be a bit of a slippery concept in that, what is positive to one person or one group may be neutral or even negative to another group. Much of teaching young people for positive creativity, therefore, involves providing the tools to decide what positive creativity means to them, and teaching them how to defend their decision. This essay focuses especially on alternative conceptions of what positive creativity means. It considers a variety of approaches, such as definitional models—objective and subjective betterment; ratings, including from layperson and experts; philosophical models—utilitarian and categorical-imperative models; decision-theory models—minimax, maximin, and maximax models; psychologically based models—a Four-C model and a model based on wise creativity. The essay also discusses steps toward teaching explicitly for positive creativity.